The antioxidant property of luteolin and its correlation among antimicrobial, hemolytic, and antiproliferative activities - de Freitas Araújo, Marcelo Gonzaga; Bauab, Tais Maria [UNESP] (My University, 2015)
Luteolin is a flavonoid found in several fruits and vegetables in significant amounts and number of biological properties of this phenolic was described, including the antioxidant activity. Several biological activities protect against the harmful action of reactive oxygen species (ROS), and here we focused our attention on the relationship between the biological activities of luteolin and their antioxidant properties. In this study, the antioxidant, antimicrobial, hemolytic and cytotoxicity activities were evaluated. Significant antioxidant activity was demonstrated and luteolin was effective against all bacteria and Candida strains tested, and showed an ability to inhibit hyphal formation. Non-hemolytic and antiproliferative activity could be demonstrated. The flavonoid showed a significant antioxidant activity, and it seems be essential for antibacterial, antifungal, non-hemolytic and antiproliferative activities.